The Economics of Shadow Economy in Real Estate: The Case of Greece (International Journal of Scientific Research and Management (IJSRM), 2025)
The paper attempts to measure and report the extent and magnitude of Shadow Economy in Real Estate in Greece. The present research analyzed the sale prices of residential real estate for the years 2018 and 2022. In the first phase, the sale price per square meter was determined for the houses for sale, in particular apartments and detached houses, through websites of real estate ads for sale. In the second phase, the average sale price per square meter was determined for the same years, through the analysis of sales contracts as they are recorded in detail in the application of the Greek Ministry of Finance, the "Register of Real Estate Transfer Values". The comparison that followed showed that the percentage difference between these two figures is related to the shadow economy. From 2018 to 2022, the shadow economy in real estate shows a clear trend of decline, although it is still high. From 49.38% estimated to hide the real sale value in 2018, it decreased to 39.48% in 2022, not counting any discounts made. In 2018 the amount of the declaration of actual sales values was estimated at € 614.6 million and in 2022 at € 728.7 million. At the same time, a quantitative survey was conducted on a random sample of 715 people in order to estimate the percentage of achieving a discount between the buyer and seller with a period of the last five years. The conclusion is that the discount rate in the majority ranges up to 5% especially in recent years, while rates up to 10% are noted on old properties. The above amount of deduction must be taken into account for the final determination of the estimated shadow economy in the real estate market. Also identified were those properties that were sold with a significant difference from their objective value, i.e. over € 100,000.00 and over € 200,000.00, an important indication for "laundering" non-taxable and / or dirty money. In 2018, money laundering was estimated at €192.5 million to €231 million and in 2022 at €227 million to €303 million.